Predicting Species Distribution for True Indigo (Indigofera tinctoria L.) in Citarum Watershed, West Java, Indonesia - Didi Usmadi; Sutomo Sutomo; Rajif Iryadi; Siti Fatimah Hanum; I Dewa Putu Darma; I Putu Agus Hendra Wibawa (Journal of Tropical Biodiversity and Biotechnology, 2021)
Citarum watershed is a region of approximately 6,610 km2 in West Java, Indonesia. Citarum watershed has been degraded through historical land use and vegetation clearing. Rehabilitation of Citarum watershed uses Indigofera tinctoria L. that has value as a source of natural blue dye and is considered suitable for the region. Species distribution modelling and Habitat suitability index (SDM/HSI) were undertaken for I. tinctoria. The occurrence and environment data (bioclimatic, topography, and soil type) were input to HSI. Results of the Indigofera tinctoria habitat suitability model in Citarum watershed are very good (0.9–1) for some parts of the Citarum watershed. The medium and high suitability areas were respectively 4.49% and 4.37% of the area were located in the lowlands (Bekasi Regency and Karawang Regency). Prediction based on climate modelling for 2050 and 2070 estimated that the medium-high suitability area of Indigofera tinctoria will be reduced relative to the present.